The safety factor of a heterogeneous slope in an open-pit metal mine: A case study from the Tanjianshan gold mine - Zhao, Xingdong; Zhao, Yifan; Yu, Wenlong (Frontiers in Earth Science, 2023)
A landslide of the north open-pit (323N) and the stability and design optimization of the south open-pit (323S) slope in the 323 belts of the Tanjianshan Gold Mine were studied. On September 14, 2020, a large landslide occurred on the east side of 323N, which posed a severe threat to the safety production of the mine. To avoid a similar slide on the south open-pit in the 323S, the limit equilibrium method was used to estimate the stability of the final slope of the designed initially open-pit in the 323N. The results show that the location and scale of the landslide are in good agreement with the three-dimensional laser scanning data. The effectiveness of the limit equilibrium method in slope stability analysis of the Tanjianshan Gold Mine was validated. The stability of the final slope of the initial design of 323S was analyzed. The sensitivity of the safety factor of homogeneous slope and heterogeneous rock slope to the bench face angle (BFA) and the difference of landslide type were compared and studied. When the spatial geometric relationship of rock masses with different lithology is complex, the engineering analogy method is inapplicable to calculation of parameters such as the BFA of heterogeneous rock slope and overall slope angle of the open-pit. The slope safety factor should be checked, and the slope step parameters are warranted to be optimized. The safety and economic benefits of the slope can be improved.